The Cost of Broken Promises or How Policy Failure Can Help Win Elections - Immigration and the 2015 UK General Election - James Hampshire (Revue Française de Civilisation Britannique)
Do policy failures inevitably lead to electoral punishment? This paper examines the role of immigration in the 2015 UK general election to argue that policy failure can be electorally successful. In the 2010 election, the Conservatives had committed to reduce net migration to under one hundred thousand. As majority partners in the 2010-15 Coalition government, they failed spectacularly to achieve this, overseeing a substantial increase in net migration. By 2015 immigration was highly salient and the electorate wanted it reduced. The paper argues that the Conservatives won a majority not despite their migration policy failure, but in large part because of it. Their failure to reduce immigration and address public anxiety contributed to the emergence of UKIP as an anti-immigration party, a development which disproportionately harmed Labour in the 2015 election. UKIP’s anti-immigration message helped the Conservative win victories in a number of key marginal constituencies, thus contributing to their unexpected majority.